2021
DOI: 10.1038/s41536-021-00121-7
|View full text |Cite
|
Sign up to set email alerts
|

Levetiracetam treatment leads to functional recovery after thoracic or cervical injuries of the spinal cord

Abstract: Spinal cord injury (SCI) leads to dramatic impairments of motor, sensory, and autonomic functions of affected individuals. Following the primary injury, there is an increased release of glutamate that leads to excitotoxicity and further neuronal death. Therefore, modulating glutamate excitotoxicity seems to be a promising target to promote neuroprotection during the acute phase of the injury. In this study, we evaluated the therapeutic effect of a FDA approved antiepileptic drug (levetiracetam-LEV), known for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 51 publications
2
12
0
Order By: Relevance
“…Next, based on the clinical evidence of mHTT pathology in the spinal cord (25), we explored 11 C-UCB-J binding in the cervical spinal cord of symptomatic heterozygous mice and observed a decline in SV2A density with a similar magnitude to the brain. Altogether these observations support the exploration of SV2A PET imaging as synaptic integrity marker in spinal cord-related disorders, for instance, amyotrophic lateral sclerosis as well as spinal cord injury (SCI), currently being investigated in our group and supported by the recent evidence that levetiracetam treatment leads to functional recovery in SCI models (34).…”
Section: Discussionsupporting
confidence: 79%
“…Next, based on the clinical evidence of mHTT pathology in the spinal cord (25), we explored 11 C-UCB-J binding in the cervical spinal cord of symptomatic heterozygous mice and observed a decline in SV2A density with a similar magnitude to the brain. Altogether these observations support the exploration of SV2A PET imaging as synaptic integrity marker in spinal cord-related disorders, for instance, amyotrophic lateral sclerosis as well as spinal cord injury (SCI), currently being investigated in our group and supported by the recent evidence that levetiracetam treatment leads to functional recovery in SCI models (34).…”
Section: Discussionsupporting
confidence: 79%
“…A sharp increase in extracellular glutamate levels has been detected in both CNS injury models and human patients, and this increase represents the cumulative effect of several pathological events that lead to the overstimulation of glutamate receptors and the occurrence of large cation fluxes (Lima et al, 2021 ). Glutamate excitotoxicity plays an important role in the development of secondary CNS injury.…”
Section: Reactive Astrocytesmentioning
confidence: 99%
“…A better understanding of the changes occurring in mitochondrial morphology and function after CNS insult may yield novel strategies for the treatment of CNS injuries. Baicalin and LEC were shown to stabilize astrocytes after injury and increase their glutamate uptake, effects that can reduce excitotoxicity and protect both neurons and oligodendrocytes (Song X. et al, 2020 ; Lima et al, 2021 ). Agathisflavone and ganglioside GM1 promoted the neuroprotective effect of astrocytes (de Amorim et al, 2020 ; Finsterwald et al, 2021 ).…”
Section: Strategies For Astrocyte-targeted Therapymentioning
confidence: 99%
“…Motor neuron quantification was performed as previously described [19], every 200 µm both rostrally and caudally from the lesion epicenter, -2000 µm rostrally to the lesion site and 2000 µm caudally to the lesion site. Spinal cord transversal cross-sections were stained with the primary antibody anti-NeuN (1:200; Millipore, Darmstadt, German) and the secondary anti-body Alexa FluorTM 594 goat anti-mouse IgG (1:1000; Invitrogen, Paisley, UK).…”
Section: Quantification Of Motor Neuronmentioning
confidence: 99%
“…To assess if Baclofen administration could lead to -motor neurons preservation after SCI, we performed an immunostaining with anti-NeuN antibody for the four experimental groups (Figure 3A). The -motor neurons were quantified in the ventral horn of the spinal cord, 2 mm rostrally and 2 mm caudally to the lesion site, nine weeks after the injury, as previously described [19] (Figure 3B). The quantification of -motor neurons revealed that there were no differences between the experimental groups (Figure 3B).…”
Section: Baclofen Administration Does Not Increase the Number Of -Mo...mentioning
confidence: 99%